Ekoantropologia antyhumanistyczna. Przypadek Johna Nicholasa Graya - Piotr Domeracki (Studia Ecologiae et Bioethicae)
Antihumanistic eco-anthropology. The case of John Nicholas Gray This article presents an outline of John Nicholas Gray’s position on the humanistic paradigm in the philosophical anthropology and ethics taken from a radically environmental perspective. It is rather hard to say that he proposes any systematized, comprehensive, coherent, and conclusive eco-philosophical theory for two reasons: firstly, his thoughts look like they were intentionally or accidentally chaotic, expressed sharply and resolutely, at times even openly provocative, far from philosophical refinement, flair, and seriousness. Secondly, his concept resembles a personal manifesto and is kept in a journalistic style. Regardless of that, I try to reconstruct, systematize, and present Gray’s view on environmental protection, human nature, the subjectivity of humans, the moral status of animals in comparison to humans, the most probable future of humankind and our planet, the issue of the validity of ethical discourse and moral practices arising from it, and finally a mistrust towards the moral progress of humanity. The central point of my essay around which the whole critical reconstruction is organized is Gray’s concept of “straw” subject. It is defined by Gray, referring to ancient Chinese ceremony, as an equivalent of the actual state of human subjectivity that, according to the English philosopher, in reality, there is no difference between people and other animals. Consequently, Gray concludes that we are the same animals as others and, what directly results from it, that human morality is nothing more than a useful fiction, while ethics can be compared only to the ordinary bourgeois novel and hence treated as “an art of hypocrisy.” Gray recommends as the only acceptable form of ethics an animal virtue (because there is nothing similar to any human virtue). This approach consists of the following principal assumptions, main aspects, provided solutions, and suggested directions of constantly practice-oriented thinking: radical anti-metaphysicism, anti-anthropocetrism, anti-humanism, naturalism, atheism, counter-progressivism, anti-scientism, biocentrism (gaism), animalism, and finally environmentalism. Gray’s anti-humanistic eco-anthropology leads us in the end to a sombre, pessimistic vision of the post-humankind that a highly probable destiny is mass destruction if human beings do not come to their senses in time becoming the straw subjects.